Ādhāra varase anarādhāra - Dave, Nānubhāī (Svāminārāyaṇa sāhitya granthamāḷā, 1978)
Episodes related to Swami Sahajānanda, 1781-1830, founder of the Svāminārāyaṇa sect of Hinduism and other religious leaders of the sect.